Total Carbohydrate Content Test of Banana Kepok (Musa Paradisiaca L.) On different steaming processes as an alternative energy source - Sri Nurindah Bakari; Sunarto Kadir; Ulfa Aulia (Universitas Muhammadiyah Palu, 2026)
Banana ( Musa paradisiaca L.) is one of the local foods that has a high carbohydrate content and has the potential to be developed as an alternative energy source. Carbohydrates act as the main source of energy for the body. However, processing processes such as steaming can affect the carbohydrate content due to changes in starch structure during gelatinization and reshaping starch structure. The formulation of the problem in this study includes what is the difference in carbohydrate content in 2 variations of steaming time, as well as the most optimal steaming time in maintaining carbohydrate content. This study aims to analyze the effect of steaming time on the total carbohydrate content of kepok bananas and assess its potential as an alternative energy source. This study also fills a research gap related to the effect of specific steaming duration on carbohydrate stability in local foods. The research uses a laboratory experiment design with a post-test only design. The sample was in the form of physiologically ripe kepok bananas steamed at a temperature of ±100°C with a time variation of 30 and 35 minutes. Carbohydrate content analysis was conducted using the Luff-Schoorl method (SNI 01-2891-1992) and tested with Mann-Whitney (?=0.05). The results showed average carbohydrate content of 36.66% (30 minutes) and 35.85% (35 minutes). The statistical test showed a value of p = 0.05 which was at the limit of significance, thus showing a tendency for difference but not statistically strong enough. It was concluded that 30-minute steaming tended to better maintain carbohydrate levels, although further research with larger samples is needed.